No, Not That Way, the Other Way: Creating Active Sites in Self-Assembled Host Molecules - Hooley, Richard J. (Synlett, 2020)
This Account describes our efforts over the last decade to synthesize self-assembled metal–ligand cage complexes that display reactive functional groups on their interiors. This journey has taken us down a variety of research avenues, including studying the mechanism of reversible self-assembly, analyzing ligand self-sorting properties, post-assembly reactivity, molecular recognition, and binding studies, and finally reactivity and catalysis. Each of these individual topics are discussed here, as are the lessons learned along the way and the future research outlook. These self-assembled hosts are the closest mimics of enzymes to date, as they are capable of size- and shape-selective molecular recognition, substrate activation and turnover, as well as showing less common ‘biomimetic’ properties such as the ability to employ cofactors in reactivity, and alter the prevailing mechanism of the catalyzed reactions.1 Introduction2 Paddlewheels and Self-Sorting Behavior3 First-Row Transition-Metal-Mediated Assembly: Sorting and Stereochemical Control4 Post-Assembly Reactivity5 Molecular Recognition and Catalysis6 Conclusions and Outlook
Keywords: molecular recognition; enzyme mimicry; self-assembly; catalysis; coordination complexes; host–guest chemistry